Hollywood Superheroes as Guardians of the Capitalist System: The Case of Superman - (:unkn) unknown (MARMARA UNIV, FAC COMMUNICATION, 2019)
Superheroes, created in comics at the end of the 19th century, appear in cinema in the second half of the century. The Superman and Mole Man (1951) which was the first feauture-length superhero movie in Hollywood was followed by many other super hero films, the most popular ones being Batman, Iron Man, Spider-Man, and Captain America. These films differ in terms of their shooting dates, pilots, actors and technical facilities. But beyond all these differences, the question of whether there is a basic narrative structure that is common in all films and what the function of this structure in popular culture is worth thinking about. To find the answer to this question, this study is focused on the possibility of a common formula or model that all super hero movies share in terms of structure and discourse, and this possibility analyzed through the movies Superman and The Mole Man (1951), Superman (1978), Superman II (1980), Superman III (1983), Superman IV: The Quest for Peace (1987), Superman Returns (2006) and Man of Steel (2013). The structural analysis of these movies is provided throughout the study, and the threats in the film stories and the solutions to these threats were discussed. In this way, the common model and discourse of the superhero movie narratives and repeated narrative phases of these films are searched. The efforts to maintain American values and lifestyle and the invisible presence of the capitalist system were examined in these films, all of which were produced in Hollywood, in terms of the concepts of Hollywood, identification, ideology, star system and popular culture through the use of structural and discourse analyses.
Keywords: Superman; Capitalism; Hollywood; Identification; Classic Narrative Cinema; Star System; Popular Culture; Superhero